Developing speaking skills through task-based learning - Sabirova Nigora, Ahadova Hulkaroy (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
For several decades now, teaching English both as a subject and as a language becomes most common. Clear pronunciation, active listening and to high lights that various activities/debates and so on were regularly arranged or not. By researches of Pakistan N.W.F.P was questionnaire from first and second year student. The questions were created by experts of previous field. Then results of questionnaire were analyzed in percentages. According to students perspective: most of students were not satisfied by their teachers. The reason of is passive teaching methods. It includes and teaches English as subject, but not as language. They prepare students just to pass their exam, does not created opportunities for improving communication skill, and less amount of time to practice language in activities and exercise. However, the responsibility of learning communication skills is equal both in teachers and students. To take good results from students speaking required to pay attention to word stress, quality of pronunciation and having basic knowledge of grammar. Creating friendly atmosphere helps to break language barrier and speak freely. It is highly supported the method of teaching by IT technologies.